Developmental and demographic differences in youth self-efficacy for fruit and vegetable consumption and proxy efficacy for fruit and vegetable availability - Geller, Karly Scott-Hillis (Kansas State University, 2008)
Consumption of fruits and vegetables (FV) contributes to healthy growth and development among youth. For effective intervention development, an understanding of the underlying casual influences on consumption is needed. The current dissertation is intended to identify whether influences on youth fruit and vegetable consumption (FVC) vary by age, gender, ethnicity and socioeconomic status (SES). The series of four chapters focus on self-efficacy for FVC and proxy efficacy to influence other adults to provide supportive FV environments. Chapter One reviews studies examining the influences on youth FVC. Consistently across studies, FV preferences and FV availability influenced youth FVC. Chapter Two and Chapter Three report studies documenting that children's confidence (proxy efficacy) to influence parents to make FV available and to influence other adults (after-school staff) to make FV available are independent but related constructs to self-efficacy to eat fruits and self-efficacy to eat vegetables. Differences were found in these constructs according to school demographic variables and youth demographic variables. Chapter Two reports that youth attending elementary schools with lower concentrations of racial/ethnic diversity and higher concentrations of high SES were more confident in influencing their parents to make FV available than youth attending schools with higher concentrations of racial/ethnic diversity and higher concentrations of low SES. Although analyses of cross sectional data collected on elementary-aged youth presented in Chapter 3 showed no demographic differences at the school level, Chapter Four examined longitudinal data across sixth-, seventh- and eighth-grade and found demographic differences using youth level variables. Across the middle school years, youth declined in proxy efficacy and racial/ethnic minority youth declined at a significantly faster rate than white youth. Each year, male and lower SES youth were significantly lower in proxy efficacy than females and higher SES youth, respectively. Thus, school or youth demographic differences in self-efficacy and proxy efficacy may contribute to the understanding of why males and lower SES youth eat less FV than females and higher SES youth.
Keywords: Self-efficacy; Fruit and vegetable consumption; Demographic differences; Proxy efficacy; Health Sciences, Nutrition (0570); Health Sciences, Public Health (0573)